Dynamics of Local Culture-Based Tourism Policy in the Digital Era: A Case Study of Kajang District, Bulukumba Regency - Nasir Nasir (International Journal of Tourism Management and Hospitality, 2025)
Tourism based on local culture is one of the important approaches in the management of the tourism sector in Bulukumba Regency, especially in Kajang District. This study aims to analyze the dynamics of local culture-based tourism policies in the digital era and their impact on cultural preservation and tourism development. The method used in this study is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the local culture-based tourism policy in Kajang District has shown significant progress in cultural preservation, although it still faces challenges related to the acceptance of digital technology by indigenous peoples. The use of digital technology can accelerate the promotion of local culture, but it also risks leading to the commercialization of culture that is not in accordance with the original values. Therefore, wise policies are needed to integrate digital technology in tourism management without sacrificing cultural preservation. This research is important as a basis for developing more adaptive and inclusive policies in advancing culture-based tourism in the area.